Nursing Students’ Communication Skills and Styles of Coping with Stress: A Public University Case - Yildirim, Belgin; Özkahraman-Koç, Şükran (Eastern Journal of Medical Sciences, 2019)
Aim: This study was conducted to identify nursing students’ communication skills and styles of coping with stress. Methods: A total of 922 nursing students participated in the study, which was designed as cross-sectional research. The data were collected using the Sociodemographic Characteristics Data Form, the Communication Skills Scale (CSS) and the Stress-Coping Styles Scale (SCSS) in 2017. Higher scores from the CSS and the SCSS indicated higher levels of communication skills and stress-coping methods. The data were analysed using SPSS for Windows (version 18.0). Results: The total score from the CSS was 124.09 ± 14.94 (min. 45, max. 225). The average of the total CSS scores of the nursing students was found to be low (124.09 ± 14.94). Out of the sub-scales of the SCSS, the highest score was for the Self-Confident sub-scale (19.87 ± 3.18) and the lowest score average was for the Seeking Social Support sub-scale (7.81 ± 2.25). Conclusion: The curricula should be developed in manner that ensures the effective development of nursing students’ communication skills which will help them solve their social and psychological problems.